PERANCANGAN DASHBOARD MONITORING KINERJA OPERASIONAL BERBASIS SUPPLY CHAIN OPERATIONS REFERENCE (SCOR) PADA KEDAI KOPI HALAMAN PERTAMA - Yeremia Batistuta; Waspada Tedja Bhirawa; Indramawan Indramawan; Darmawan Yulianto (Jurnal Teknik Industri Universitas Dirgantara Marsekal Suryadarma (Unsurya), 2026)
This study aims to design an operational efficiency monitoring dashboard based on the Supply Chain Operations Reference framework at Kedai Kopi Halaman Pertama. The research uses operational data from July to December 2025, which were processed and visualized using Power BI. The results show that the dashboard is able to present operational performance information in a structured manner and assist the business owner in monitoring cost efficiency and service time. The proposed dashboard can be utilized as a data-driven monitoring tool to support more systematic and measurable operational decision- making in small and medium enterprises.